2011
DOI: 10.1111/j.1467-9671.2011.01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality of an online geocoding resource in the context of a large Brazilian city

Abstract: Geocoding urban addresses usually requires the use of an underlying address database. Under the influence of the format defined for TIGER files decades ago, most address databases and street geocoding algorithms are organized around street centerlines, associating numbering ranges to thoroughfare segments between two street crossings. While this method has been successfully employed in the USA for a long time, its transposition to other countries may lead to increased errors. This article presents an evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…However, elsewhere an apparent inverse relationship between geocoding outcomes and area deprivation has been observed at local level in other LMICs. A study in the Brazilian city of Belo Horizonte, for example, found that geocoding precision via the Google geocoding API was lower in slum areas than in formal urban neighbourhoods [ 51 ]. In response to this issue, the What3Words georeferencing system, which uses an algorithm to assign three words as a unique, human-friendly georeference to each of 57 trillion grid squares globally, has been used to locate addresses in Brazilian favelas lacking conventional addressing systems [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, elsewhere an apparent inverse relationship between geocoding outcomes and area deprivation has been observed at local level in other LMICs. A study in the Brazilian city of Belo Horizonte, for example, found that geocoding precision via the Google geocoding API was lower in slum areas than in formal urban neighbourhoods [ 51 ]. In response to this issue, the What3Words georeferencing system, which uses an algorithm to assign three words as a unique, human-friendly georeference to each of 57 trillion grid squares globally, has been used to locate addresses in Brazilian favelas lacking conventional addressing systems [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used a much less sophisticated modeling approach, which was unable to consider synergies among changes. Concerning distance calculation, another limitation is related to some inaccuracy in Google Maps in Brazil, especially in lower income areas ( Davis Junior and de Alencar, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The power of the crowd is well known and it can sometimes be used to derive information that was impossible or at least impractical to obtain by other means. The potential of crowdsourcing has been noted in geography and associated geospatial sciences with numerous examples of its use (Basiouka and Potsiou , Davis and de Alencar , Girres and Touya , Goodchild , Heipke , Neis et al. ).…”
Section: Introductionmentioning
confidence: 99%